Beyond summerland - Lecoat, Jenny (Graydon House, 2024)
After World War II liberation of Jersey in the Channel Islands, 19-year-old Jean Parris discovers that a teacher who lives above her father's shop might be responsible for his wartime arrest and sets out to uncover the truth.